Characterization of Nano Tetrakis(4-sulfonatophenyl)porphyrin Aggregation Through Atomic Force Microscopy and UV-Vis Spectroscopy Methods - RAHIMI, RAHMATOLLAH; JEDDI, MARYAM; MOHAMMAD REZA RAVANFAR, SAYYED (Asian Journal of Chemistry, 2010)
The biological roles of porphyrins and metalloporphyrins as biological model compounds are known since the significant biological macromolecules like hemoglobin and chlorophyll were discovered. The known biological roles for these compounds are in photosynthesis and respiration processes. In addition, the porphyrins have been applied at different fields such as photoconverter, photocatalysts, photosensitizes in diagnosis and photodynamic therapy and also, as an anti Aids (HIV) drugs. In this work the tetrakis(4-sulfonatophenyl)-porphyrin (TPPS4) was synthesized and metallated according to the reference method, for this compound is very active model of biological porphyrins. The aggregations of TPPS4 in acidic solution were investigated by two methods, atomic force microscopy (AFM) and ultra violet -visible spectroscopy (UV-Vis). The synthesized compound of TPPS4 was deposited on the surface of glass and the spatial structure was imaged by scanning on atomic force microscopy. The size of nanotubes calculated by section analysis was about (20 nm × 100 nm × 200 nm). Atomic force microscopy confirmed the J-aggregations of TPPS4. The UV-Vis spectroscopy method was also used for investigation of TPPS4 aggregation. The measured UV-Vis spectrum of the aggregated form of the compound in acidic solutions has shown maximum absorption at 433, 490 and 705 nm, which has to be attributed to the formation of J-aggregates (490 nm). The synthesized TPPS4 nanotubes can be used in future as electronic devices.